2021
DOI: 10.21608/edj.2021.85335.1713
|View full text |Cite
|
Sign up to set email alerts
|

Root and Root Canal Morphology of Permanent Mandibular Anterior Teeth in a Sample of Egyptian Population

Abstract: Objectives:The aim of this work was to study the morphology of root and root canals of permanent mandibular anterior teeth in a sample of the Egyptian population.Methods: A total of 16 permanent mandibular central incisors (I1), 25 permanent mandibular lateral incisors (I2) and 15 permanent mandibular canines (C) were collected and classified into groups according to shape and number of roots. Molds of pink wax with the samples were submitted for cone beam computed tomography (CBCT). The number and shapes of r… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1

Citation Types

0
0
1

Year Published

2023
2023
2023
2023

Publication Types

Select...
1

Relationship

0
1

Authors

Journals

citations
Cited by 1 publication
(1 citation statement)
references
References 20 publications
0
0
1
Order By: Relevance
“…Studies on root canal anatomy of mandibular canine in Egyptian population is scarce, one study 43 examined a very small sample size (15 mandibular canines), even though they showed approximated percentage to our study for a second canal 33.3% with 13.3% for Vertucci type III, 13.3% IV and 6.7% V, this sample size cannot reflect a prevalence in a subpopulation. Another study 44 evaluated mandibular anterior teeth bilaterally in 100 patients with contradictory results to the present study as they concluded a 100% for Vertucci type I for mandibular canines with total absence of a second canal 44 , this could be attributed to the sample size which is one tenth of the current study sample size.…”
Section: Discussioncontrasting
confidence: 60%
“…Studies on root canal anatomy of mandibular canine in Egyptian population is scarce, one study 43 examined a very small sample size (15 mandibular canines), even though they showed approximated percentage to our study for a second canal 33.3% with 13.3% for Vertucci type III, 13.3% IV and 6.7% V, this sample size cannot reflect a prevalence in a subpopulation. Another study 44 evaluated mandibular anterior teeth bilaterally in 100 patients with contradictory results to the present study as they concluded a 100% for Vertucci type I for mandibular canines with total absence of a second canal 44 , this could be attributed to the sample size which is one tenth of the current study sample size.…”
Section: Discussioncontrasting
confidence: 60%